2018
DOI: 10.1080/17588928.2018.1513399
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity-driven memory enhancement persists over time but does not benefit from post-learning sleep

Abstract: Sleep-dependent memory processing is dependent on several factors at learning, including emotion, encoding strength, and knowledge of future relevance. Recent work documents the role of curiosity on learning, showing that memory associated with high-curiosity encoding states is retained better and that this effect may be driven by activity within the dopaminergic circuit. Here, we examined whether this curiosity effect was enhanced by or dependent on sleep-related consolidation. Participants learned the answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 58 publications
12
61
7
Order By: Relevance
“…The momentary experience of curiosity can be seen as a motivational state that facilitates knowledge acquisition (Silvia & Kashdan, 2009; Gottlieb and Oudeyer, 2018). Consistent with this idea, studies have shown that states of high curiosity enhance long-term memory (Kang et al, 2009; Gruber et al, 2014; McGillivray et al, 2015; Marvin and Shohamy, 2016; Stare et al, 2018; Galli et al, 2018). Furthermore, recent neuroimaging evidence suggests that state curiosity enhances memory via increased activation in the mesolimbic dopaminergic circuit including the hippocampus (Gruber et al, 2014; Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…The momentary experience of curiosity can be seen as a motivational state that facilitates knowledge acquisition (Silvia & Kashdan, 2009; Gottlieb and Oudeyer, 2018). Consistent with this idea, studies have shown that states of high curiosity enhance long-term memory (Kang et al, 2009; Gruber et al, 2014; McGillivray et al, 2015; Marvin and Shohamy, 2016; Stare et al, 2018; Galli et al, 2018). Furthermore, recent neuroimaging evidence suggests that state curiosity enhances memory via increased activation in the mesolimbic dopaminergic circuit including the hippocampus (Gruber et al, 2014; Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…This obviously made the target's face more distinctive, but weapon scene participants may have been particularly curious as to the motivations and mental state of this odd-looking assailant, causing them to pay closer attention to his face than the noweapon counterparts. Curiosity has been described as an exploratory drive to resolve incongruities between knowledge and experience (Stare, Gruber, Nadel, Ranganath, & Gómez, 2018), and the drawing of a deadly weapon by an unassuming actor in an otherwise mundane scenario may, for some viewers at least, be an example of this incongruence. As high curiosity encoding states are known to enhance memory (Gruber, Gelman, & Ranganath, 2014;Kang et al, 2009;Marvin & Shohamy, 2016), it is conceivable that distinctive or otherwise intriguing perpetrators may sometimes neutralise or even reverse WFEs among curious witnesses.…”
Section: Discussionmentioning
confidence: 99%
“…As many of our questions included topics associated with educationally-relevant content, our results suggest that children and adolescents who are curious about a question are indeed more likely to remember the associated answer. Memory benefits associated with states of high curiosity have been demonstrated after longer delays in adults (Gruber et al, 2014;Kang et al, 2019;Stare et al, 2018) and future studies are needed to test their persistence in children and adolescents over extended periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…To induce curiosity, we used a trivia paradigm in which participants consecutively encoded trivia questions that were associated with varying degrees of curiosity and anticipated the correct answer (see Figure 1). Studies with adults have repeatedly shown that answers to trivia questions associated with high curiosity are better remembered than answers to low-curiosity trivia questions (Fastrich et al, 2018;Galli et al, 2018;Gruber et al, 2014;Kang et al, 2009;Marvin & Shohamy, 2016;McGillivray et al, 2015;Stare, Gruber, Nadel, Ranganath, & Gómez, 2018;Wade & Kidd, 2019). The paradigm consisted of a screening phase in which we selected participant-specific trivia questions for which the answers were unknown and which varied in subjective curiosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation